Examining the role of the learner and the teacher in language learning motivation. (January 2023) - Hennebry-Leung, Mairin; Xiao, Hu Amy
Effective teaching practice requires that teachers know their students not as 'faceless average learners', but as individuals. The most individual of learner characteristics is personality, and yet language education research has made little progress in understanding the role of personality. As the field of language learning motivation seeks to develop frameworks for motivational teaching practice, a richer understanding of learners' individuality is crucial in shaping practices that respond to learners' needs. The present study examines the role of learners' personality and teachers' practice in shaping motivation and self-efficacy in language learning. Drawing on data gathered from 277 learners of English in Hong Kong, aged 11–14 years, and 24 lesson observations, across 10 classes, the study applies hierarchical multiple regression analysis to reveal a significant role of personality and teachers' motivational practice in predicting language learning motivation and self-efficacy. Results reveal that while personality variables demonstrated large effect sizes for motivational orientations, teacher practice variables evidenced large effect sizes for language learning self-efficacy. Implications are discussed for theorization of language learning motivation and for teaching practice, with a particular emphasis on language teacher education.